Pengaruh Penggunaan Media Let’s Read terhadap Kemampuan Memahami Bacaan pada Siswa Kelas IV Mata Pelajaran Bahasa Indonesia - Sabrina Abnoor Pasaribu; Nurmayani Nurmayani; Zainuddin Muchtar; Halimatussakdiah Halimatussakdiah; Fajar Sidik Siregar (Jurnal Keluarga Sehat Sejahtera, 2026)
The purpose of this research is to determine the effect of using the Let’s Read media on reading comprehension skills among fourth-grade students in the Indonesian Language subject at SDN 101777 Saentis for the 2025/2026 academic year. This study uses a quantitative approach with a quasi-experimental design method, specifically a non-equivalent control group design. The population in this study consists of all fourth-grade students divided into two classes, namely class IV-A as the experimental class and class IV-B as the control class, each with 16 students, resulting in a total sample of 32 students. The research instrument used was a test in the form of essay questions consisting of 10 questions for the pre-test and 10 questions for the post-test. The results of the data analysis showed that the average post-test score of the experimental class was 85, higher than the control class at 68.75. Based on the t-test results, the calculated tvalue was 5.439 and the  ttable Value was 2.042 at a significance level (Sig.) of 0.05, thus H0 was rejected and Ha was accepted. Thus, it can be concluded that the use of the Let’s Read media has a significant effect on the reading comprehension ability of fourth-grade students in the Indonesian language subject, narrative text material, at SDN 101777 Saentis for the 2025/2026 academic year.